Analisis Sistem Pengendalian Internal Kas pada Masjid Al – Mukarromah Kota Samarinda - Sansibar Octapatika; Sri Mintarti; Salmah Pattisahusiwa (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
The mosque is part of the public entity and all related activities must be answerable to the public. Transparency and accountability is very important so that it can be useful for other public entity and the parties outside of the people who are included. The mosque is a non-profit organization that is very different from other organizations because there are still many perceived that the mosque managed people who are not professional or as a professional organization. The Mosque Al-Mukarromah has the scope of a small cash and have a small human resources and in terms of the latter hailed can not be known. This research aims to find out how the  internal control system upon receipt of cash and cash equivalents at the mosque Al-Mukarromah spending. The types of data that is used is a secondary data and primary data. Analysis Tool that is used is a descriptive qualitative. Based on the results of research analysis system and procedures cash spending Al-Mukarromah Mosque has not yet been fully meet the elements of internal control because there are still elements of internal control in the mosque that is not yet fully done among other things in the storage function and the recording should only be performed by a separate treasurer, cash balance that is in the hands of the stored in the wallet and brought up by the treasurer, rarely done rekonsialisai bank by treasurer, there is no formation small cash fund for expenditures which nominally relative small and do not physical pencocokkan cash which is in the hands of the according to note periodic so that the possibility of fraud is still a very big.Keywords:  Internal Control System